EFFECT OF PUBLIC SERVICE MOTIVATION AND COMPETENCE ON STAFF PERFORMANCE WITH PROFESSIONALISM AS INTERVENING VARIABLE - Ashari, Laeli; Thamrin , Mohammad; Sanosra, Abadi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to examine the effect of public service motivation and competence on staff performance with professionalism as an intervening. Method: This research can be classified as explanatory research. The research population was all 80 staff at the Jember Regency Regional Disaster Management Agency (BPBD) and sampling used saturated sampling. The analytical model used in this research is Structural Equation Modeling (SEM) analysis with the help of WarpPLS software. Results: Results of the research state that public service motivation and competence has significant effect on the professionalism. Competence has significant effect on the staff performance. Public service motivation has insignificant effect on the staff performance. Professionalism has significant effect on the staff performance. Public service motivation and competence has significant effect on the staff performance, mediated by professionalism. Novelty: This research tries to test a model related to human resources performance by involving public service motivation and professionalism as intervening.